2012
DOI: 10.1089/aid.2011.0396
|View full text |Cite
|
Sign up to set email alerts
|

HIV Type 1 Coreceptor Tropism, CCR5 Genotype, and Integrase Inhibitor Resistance Profiles in Vietnam: Implications for the Introduction of New Antiretroviral Regimens

Abstract: In Vietnam, where an estimated 280,000 people will be HIV-positive by 2012, recommended antiretroviral regimens do not include more recently developed therapeutics, such as Integrase inhibitors (INI) and coreceptor antagonists. This study examined HIV-1 coreceptor tropism and INI drug resistance profiles, in parallel with CCR5 genotypes, in a cohort of 60 HIV-positive individuals from different regions of Vietnam. No evidence of INI resistance was detected. Some 40% of individuals had X4-tropic HIV-1, making t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…A previous report found a switch from R5 to X4 viruses during effective ART in about 50% of patients who harboured R5 viruses at baseline [23]. Reports from other countries with limited CRF01_AE samples also demonstrated a high prevalence of X4 tropism in HIV-1 CRF01_AE: 31 and 40% of patients harboured X4 virus in studies from Singapore and Vietnam, respectively [24,25] . Sequence compiling in China showed that 22% of patients harboured X4 and 40% R5X4 [26].…”
Section: Discussionmentioning
confidence: 81%
“…A previous report found a switch from R5 to X4 viruses during effective ART in about 50% of patients who harboured R5 viruses at baseline [23]. Reports from other countries with limited CRF01_AE samples also demonstrated a high prevalence of X4 tropism in HIV-1 CRF01_AE: 31 and 40% of patients harboured X4 virus in studies from Singapore and Vietnam, respectively [24,25] . Sequence compiling in China showed that 22% of patients harboured X4 and 40% R5X4 [26].…”
Section: Discussionmentioning
confidence: 81%
“…The global prevalence of CRF01-AE is 5%, and it is responsible for up to 4% of the HIV-1 infections in Europe according to the SPREAD study (13). Previous studies have employed either phenotypic or genotypic prediction of coreceptor usage by HIV-1 CRF01-AE, but the correlation between the two methods has not been investigated (14)(15)(16)(17).…”
mentioning
confidence: 99%
“…On the other hand, an IDU-associated virus already transmitted through heterosexual contact may regain some of this transmission efficacy. Though it is difficult to speculate on mechanisms that might bring about this potential difference, some unique characteristics of HIV strains in Vietnam, such as the dominance of CXCR4 tropism observed in our study or a previous report [ 23 ], may have contributed to the apparent lower sexual transmission efficacy among stable couples in northern Vietnam. However, only half of the HIV env sequences could be successfully evaluated, and sequence data of the V3 loop alone cannot determine co-receptor tropism of CRF01_AE stains [ 24 ].…”
Section: Discussionmentioning
confidence: 66%